Gödel Form of Fuzzy Transitive Relations - Beg, Ismat; Ashraf, Samina (Sarajevo Journal of Mathematics, 2024)
The concepts of fuzzy transitivity of a fuzzy relation on a given universe and the measure of fuzzy transitivity are studied with the use of Gödel fuzzy implicator. 2000 Mathematics Subject Classification. 03E72, 46S40, 68T37